Cover Feature: Long‐Term Stability of a Liquid‐Infused Coating with Anti‐Corrosion and Anti‐Icing Potentials on Al Alloy (ChemElectroChem 15/2019). Issue 15 (19th July 2019) - Zhang, Meiling; Chen, Rongrong; Liu, Qi; Liu, Jingyuan; Yu, Jing; Song, Dalei; Liu, Peili; Gao, Liangtian; Wang, Jun
Abstract : The Cover Feature shows slippery liquid‐infused porous surfaces (SLIPS), which have a unique structure that greatly reduces the loss of lubricant through volatilization or subcooled condensation. This effectively extends the life of SLIPS. The corrosion resistance of the as‐prepared SLIPS is five orders of magnitude higher than that of bare Al alloy, and did not change significantly even after extended immersion in NaCl solution. More information can be found in the Article by M. Zhang et al. onpage 3911 in Issue 15, 2019 (DOI:10.1002/celc.201900302 ).